Value-added assessment in practice : lessons from the Pennsylvania value-added assessment system pilot project - McCaffrey, Daniel F.; Hamilton, Laura S., 1968-; Rand eBooks (Santa Monica, CA : RAND, 2007)
The No Child Left Behind Act of 2001 places a strong emphasis on the use of student achievement test scores to measure school performance, and, throughout the United States, school and district education reform efforts are increasingly focusing on the use of student achievement data to make decisions about curriculum and instruction. To encourage and facilitate data-driven decisionmaking, many states and districts have begun providing staff with information from value-added assessment (VAA) systems-collections of complex statistical techniques that use multiple years of test-score data to try to estimate the causal effects of individual schools or teachers on student learning. The authors examined Pennsylvania's value-added assessment system, which was rolled out in four waves, allowing comparison of a subset of school districts participating in the VAA program with matched comparison districts not in the program. The study found no significant differences in student achievement between VAA and comparison districts. The authors surveyed school superintendents, principals, and teachers from these districts about their attitudes toward and use of test and value-added data for decisionmaking, and found that most educators at schools participating in the VAA program do not make significant use of the information it provides. McCaffrey and Hamilton conclude that the utility of VAA cannot be accurately assessed until educators become more engaged in using value-added measures.
Introduction -- Methods and data -- Effects of PVAAS on student achievement -- Superintendents' responses to PVAAS -- Principals' responses to PVAAS -- Teachers' responses to PVAAS -- Summary and Implications -- Appendix: Matching results summary tables and figures.
"RAND Education."
Includes bibliographical references (p. 103-105).
Also available on the internet via WWW in PDF format.
Keywords: Educational accountability -- United States; Educational indicators -- United States; Educational tests and measurements -- Pennsylvania; Electronic books